2021
DOI: 10.1200/go.20.00587
|View full text |Cite
|
Sign up to set email alerts
|

Development and Pilot Implementation of the Genomic Risk Assessment for Cancer Implementation and Sustainment (GRACIAS) Intervention in Mexico

Abstract: PURPOSE Genomic cancer risk assessment (GCRA) is standard-of-care practice that uses genomic tools to identify individuals with increased cancer risk, enabling screening for early detection and cancer prevention interventions. GCRA is not available in most of Mexico, where breast cancer (BC) is the leading cause of cancer death and ovarian cancer has a high mortality rate. METHODS Guided by an implementation science framework, we piloted the Genomic Risk Assessment for Cancer Implementation and Sustainment (GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…All patients included in this study received GCRA and had genetic testing results available at the time of this analysis. Various methods were used for PV detection, 12 including a multigene panel test with a custom QIAseq (QIAGEN, Inc., Germantown, MD, USA) amplicon-based panel for detecting breast cancer predisposition variants (ATM, BRCA1, BRCA2, CDH1, CHEK2, NF1, PALB2, PTEN, RAD51C, RAD51D, TP53). The design includes the 5' and 3' untranslated regions, full exonal gene coverage, and extends 10 base-pairs into introns, and results in a consistent coverage of over 300-500x.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients included in this study received GCRA and had genetic testing results available at the time of this analysis. Various methods were used for PV detection, 12 including a multigene panel test with a custom QIAseq (QIAGEN, Inc., Germantown, MD, USA) amplicon-based panel for detecting breast cancer predisposition variants (ATM, BRCA1, BRCA2, CDH1, CHEK2, NF1, PALB2, PTEN, RAD51C, RAD51D, TP53). The design includes the 5' and 3' untranslated regions, full exonal gene coverage, and extends 10 base-pairs into introns, and results in a consistent coverage of over 300-500x.…”
Section: Methodsmentioning
confidence: 99%
“…The barriers to implementing genetic cancer risk assessment (GCRA) services in the country include excessive costs, lack of coverage of genetic testing within the public health system, limited awareness of the benefits of identifying PVs, and limited number of physicians with GCRA expertise. 11,12 Previous studies in Mexican BC patients unselected for family history have demonstrated that 15% of cases overall are associated with BRCA PVs. 13 The frequency of BRCA PVs was higher (>20%) among young TNBC patients in two small studies, 14,15 and this molecular subtype accounts for 16-23% of BC cases in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…A critical finding from the GRACIAS intervention is the patients’ feedback recommending the development of Spanish resources to improve learning. 78 …”
Section: Genetic Riskmentioning
confidence: 99%
“…RE-AIM is ideal for pragmatic contexts and facilitates evaluation of impact at the individual (reach/effectiveness) and institutional (adoption/implementation) levels simultaneously, since multi-level impact is critical for both translation and broader public health benefit ( Glasgow et al, 1999 ; Nilsen, 2015 ; Brownson, 2017 ; Glasgow and Estabrooks, 2018 ; Glasgow et al, 2019 ). Over the last two decades, RE-AIM has been used extensively in other contexts, yet it is only beginning to be applied to precision health ( Glasgow et al, 2019 ; Jones et al, 2021b ; Blazer et al, 2021 ; Kim et al, 2021 ; Miller et al, 2021 ; Sperber et al, 2021 ). In this study, we demonstrate the use of RE-AIM to conduct a post-hoc evaluation and report outcomes from two DNA screening programs at Geisinger with the goal of generating evidence needed for systematic implementation of DNA-based population screening.…”
Section: Introductionmentioning
confidence: 99%